Pengaruh alih fungsi lahan terhadap resiko longsor di Desa Ngadirejo - Mohammad Adam Firdaus; Mohammad Adhi Wicaksana; Mufid Zahir Hilmi; Muhammad Dimas Aqshal Syafatullah; Nafila Ratna Romaita; Queentasya Vanti Dian Kristianti; Hadi Soekamto; Alfyananda Kurnia Putra (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2021)
Ngadirejo Village is a village located in the highland area that is located at the foot of Mount Bromo. This area is also oriented to the protected forest of the Foot of Mount Bromo.But in recent years the forest area of Ngadirejo Village has been turned into fields and agricultural land due to land function switching activities carried out by the community with the aim of economic benefits. This land function transition activity has an influence for Ngadirejo Village which is a slope area from the foot of the mountain. One of them is the potential for landslides that can occur. This research serves to explain about the influence of land function transition activities on landslide potential in Ngadirejo Village.This study uses qualitative descriptive method which is a research method described in descriptive form. As well as in data collection techniques using literature studies and field observations. From the results of the study, it can be known that the production forest area in Ngadirejo Village began to switch functions as agricultural fields. Then because the soil condition of Ngadirejo Village is easily eroded and located on a steep slope, then in general Ngadirejo Village has the potential of landslides that are in the medium to high category. Desa Ngadirejo merupakan sebuah desa yang terletak di wilayah dataran tinggi yaitu terletak pada kaki Gunung Bromo. Wilayah ini juga berorientasi dengan hutan lindung dari Kaki Gunung Bromo.Namun beberapa tahun terakhir ini wilayah hutan dari Desa Ngadirejo telah berubah menjadi ladang dan lahan pertanian dikarenakan aktivitas peralihan fungsi lahan yang dilakukan oleh masyarakat dengan tujuan keuntungan ekonomi.Aktivitas peralihan fungsi lahan ini menimbulkan pengaruh bagi Desa Ngadirejo yang merupakan wilayah lereng dari kaki gunung.Salah satunya adalah potensi tanah longsor yang bisa terjadi.Penelitian ini berfungsi menjelaskan tentang pengaruh aktivitas peralihan fungsi lahan terhadap potensi longsor di Desa Ngadirejo.Penelitian ini menggunakan metode deskriptif kualitatif yaitu sebuah metode penelitian yang dijabarkan dalam bentuk deskriptif. Serta dalam teknik pengumpulan data menggunakan kajian literatur serta observasi lapangan. Dari hasil penelitian tersebut dapat diketahui bahwa wilayah hutan produksi yang ada di Desa Ngadirejo mulai beralih fungsi sebagai ladang pertanian. Kemudian dikarenakan kondisi tanah Desa Ngadirejo yang mudah tererosi serta berada di lereng yang terjal, maka secara umum Desa Ngadirejo memiliki potensi longsor yang berada pada kategori sedang hingga tinggi.